2015
DOI: 10.1111/chd.12273
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preference and Perception of Care Provided by Advance Nurse Practitioners and Physicians in Outpatient Adult Congenital Clinics

Abstract: Patient satisfaction was high regardless of whether care was provided by physicians or NPs. However, patients appear to make distinctions in what they believe the type of care each practitioner is best at providing. Patient education regarding competence of the different health care providers may continue to improve patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 17 publications
1
19
0
Order By: Relevance
“…This is consistent with the literature demonstrating that patients were very satisfied with NP health care services. [15,16,21,22,30,32,[34][35][36] Furthermore over 98% of participants would seek the services of a NP in the future. The findings also indicate that rapport building, accessibility, flexibility with scheduling and consistency of health care provider, contributed to patient satisfaction which corresponds with research findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the literature demonstrating that patients were very satisfied with NP health care services. [15,16,21,22,30,32,[34][35][36] Furthermore over 98% of participants would seek the services of a NP in the future. The findings also indicate that rapport building, accessibility, flexibility with scheduling and consistency of health care provider, contributed to patient satisfaction which corresponds with research findings.…”
Section: Discussionmentioning
confidence: 99%
“…[21] NP research and patient satisfaction is influenced by NPpatient communication, NP knowledge and access to care and overall, studies related to factors influencing patient satisfaction with NP-provided care found that patients are satisfied. [3,4,12,18,21,22] The literature generally reports that satisfaction with NP care leads to good health outcomes. [3,4] However, research specifically related to patient satisfaction with NP care within NL was absent.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The lack of clarity about the role of APNs among patients is not a phenomenon unique to the study's context. In New Zealand and the USA, healthcare consumers also felt that they lacked clarity about APNs and suggested that greater clarity would be facilitative to enhancing the use of APNs (Halcomb, Peters, & Davies, 2013; Maul et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…They also shared how they were accustomed to seeking help from doctors for medical care and asserted their preferences for doctors. From the outset, the patients tend to exclusively regard doctors as more “ experienced ” and “ qualified ” than APNs (Maul et al, 2015). This mindset, evident in this study, might be contributed by Singapore's elitist and meritocratic culture (Goh, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast, our research identified that unwillingness to consider care by a NP in some situations was grounded in a belief that NPs did not possess the knowledge and qualifications to offer appropriate care and to refer on when required. These contrasting findings suggest there remains a large proportion of the general public who are unsure as to what constitutes the NP scope of practice (Allnutt et al, ; Barratt & Thomas, ; Maul et al, ). Without this understanding, expansion and ubiquity of the NP in the provision of health care remains limited.…”
Section: Discussionmentioning
confidence: 99%